MODEL DINAMIKA PENYEBARAN PENYAKIT CAMPAK DENGAN PENGARUH MIGRASI DAN PENAMBAHAN IMUNISASI - Ainun Fatmawati; Lisnawati R. Aju; Ristina Malango (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2020)
This article discusses the dynamics of the spread of measles with the effect of giving and adding immunization. To analyze the results, a fixed point was determined to be disease-free and endemic. The analysis was carried out by considering the basic reproduction number (R0). In the analysis of the results obtained conditions R01 which indicates that the spread of measles can be prevented. By practicing and adding immunizations, the value of the numerals will be smaller, which indicates the reduction in the population.